PRAGMATIC FUNCTIONS OF PRESUPPOSITIONS: HOW PRESUPPOSITIONS SHAPE MEANING IN SPOKEN AND WRITTEN LANGUAGE - Eragamreddy, Nagamurali (Universitas Muhammadiyah Metro, 2025)
This research examines how presupposition triggers a function in storytelling and debate genres to create meaning, finding that distributions of triggers and contexts of discourse determine interpretive dynamics together. The study confirms that definite descriptions make background assumptions in Arthur Conan Doyle's A Scandal in Bohemia and a free-speech debate transcript, and genre-conventional patterns result—narrative uses low-frequency-high-impact clefts and factices to regulate reader involvement, and debate uses plentiful contrastive (